Pengaruh kompetensi, tanggung jawab dan budaya kerja terhadap kinerja pegawai negeri sipil padaDinas perdagangan dan koperasi, usaha kecil dan menengah kota solok - Yuci Mardiosa; Nurhayati Nurhayati; Netty Indrawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research was conducted at the Department of Trade and Cooperatives, Small and Medium Enterprises in the City of Solok, the purpose of this research was to determine the effect of Competence, Responsibility and Work Culture on the Performance of Civil Servants in the Office of Trade and Cooperatives, Small and Medium Enterprises of the City of Solok. In this study, the population was civil servants at the trade and cooperative service, small and medium enterprises in the city of Solo, totaling 32 people. By using total sampling, a sample of 32 people was obtained. The data collection technique used is by using a questionnaire or questionnaire. Based on multiple linear regression analysis of the variables of competence, responsibility and work culture on the performance of civil servants, Y = 6.378 a + 0.374 X1 + 0.206 X2 + 0.253 X3 + e. from the t test conducted, it was found that the variable X1 Competence had a significant effect on the performance of civil servants with a variable value of 2.957 >1,699 and a significant value level of 0.006 <0.05. Variable X2 Responsibility has a significant effect on the performance of civil servants with a variable value of 2.065 >1,699 and a significant value level of 0.003 <0.05. Variable X3 Work Culture has a significant effect on the performance of civil servants with a variable value of 2.101 > 1,699 and a significant value level of 0.045 <0.05. From the F test conducted, it was found that competence, responsibility and work culture simultaneously influenced the performance of civil servants, fcount 18.315 > ftable 2.922 with a significance value of 0.000 <0.05.